Cross-Cultural Interviewing: Challenges and Strategies - Singh, Ramanjeet; Khosla, Rajiv (Gyan Management Journal, 2007)
Successful managers in the new global business reality will be able to deal with mutiple cultural dfferences. Those  simultaneously. Not ony are there national cultures, there are ethnic, religious, and professional cultures - to name just a few. However, rather than considering cultural differnces as a problem with which one must cope, practitioners can talce this new understanding of reality as a challenge to handle the dfferences in sensitive and synergistic ways. If they can do this, they have a chance to be a step - or more -ahead of the competition. In this paper, the use of interviews across different cultural backgrounds and the potential for cultural bias are presented. Two case studies are used to illustrate the importance of cultural sensitivity in successful interyiewing. Effective techniques, which include establishing rapport with the candidate, building a rlationship, and chosing appropriate interview styles, are provided for practitioners.
Keywords: Challenges and Strategies; Successful managers; backgrounds; Effective techniques